1994
DOI: 10.1152/jappl.1994.77.1.98
|View full text |Cite
|
Sign up to set email alerts
|

Segmental bioelectrical impedance analysis: theory and application of a new technique

Abstract: Bioelectrical impedance analysis (BIA) for body composition has been based on the volume conductor model that results in the mathematical relationship Ht2/R approximately FFM, where Ht is body height, R is whole body resistance or impedance, and FFM is fat-free mass. Although this relationship exists in the human subject, its strength and usefulness have been subject to conflicting reports. This study reassessed the theory and methodology of BIA and describes a new technique for measuring segmental impedance t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
240
3

Year Published

1998
1998
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(257 citation statements)
references
References 0 publications
11
240
3
Order By: Relevance
“…23 Bioelectrical impedance and resistance measurements at 50 kHz were obtained using a multifrequency BIA instrument, Model SFB2 (SEAC, Brisbane, Australia) with current source electrodes, placed on the base of the fingers and toes, maintained in place throughout all segment measurements. This ensured that any adverse effects of inconsistent current distribution were minimal and that the sum of segment impedances was equal to whole-body impedance 20 (see Table 2); ie source electrodes were not relocated to 5 cm from the sensing electrodes, which would result in summed segmental impedances greater than whole-body impedance. 19 Sensing electrodes were placed on ankle and wrist, for whole-body measurements, and variously at the elbow, acromion (shoulder), anterior superior iliac spine (ASIS) and knee, according to the segment measurement being undertaken.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…23 Bioelectrical impedance and resistance measurements at 50 kHz were obtained using a multifrequency BIA instrument, Model SFB2 (SEAC, Brisbane, Australia) with current source electrodes, placed on the base of the fingers and toes, maintained in place throughout all segment measurements. This ensured that any adverse effects of inconsistent current distribution were minimal and that the sum of segment impedances was equal to whole-body impedance 20 (see Table 2); ie source electrodes were not relocated to 5 cm from the sensing electrodes, which would result in summed segmental impedances greater than whole-body impedance. 19 Sensing electrodes were placed on ankle and wrist, for whole-body measurements, and variously at the elbow, acromion (shoulder), anterior superior iliac spine (ASIS) and knee, according to the segment measurement being undertaken.…”
Section: Methodsmentioning
confidence: 99%
“…17 -19 In adults, although the trunk accounts for about 45% of BWt, it contributes only 10% of wholebody impedance, whereas an arm of 4% BWt contributes 46% of impedance. 19,20 This is because the arm is a relatively long and thin electrical conductor, impeding the flow of current to a greater extent than the shorter thicker trunk. It has been suggested that BIA of certain body segments may sufficiently represent whole-body impedance to be used as a proxy for this measurement when predicting body composition in adults; 18,19 especially if the whole-body measurement cannot be easily obtained because of damaged or inaccessible electrode contact sites due to burns, plaster casts etc.…”
Section: Introductionmentioning
confidence: 99%
“…Phase angle was included as an additional potential measure of soft tissue composition (Baumgartner et al, 1988). Segmental impedance measurements were made as reported by Organ et al (1994). This approach allows segmental impedance measurements (leg) without the need for proximal (segmental) electrodes.…”
Section: Body Compositionmentioning
confidence: 99%
“…Another drawback of established impedance-based method is a low sensitivity to regional, for example subcutaneous abdominal, fat. Whole body impedance contains little information about the trunk, which contributes only 5 ± 10% to total impedance 22 and this problem also holds for impedance measurement between both feet of the subject. In both cases the electrical current passes mainly through fat-free, highly conducting tissue; only in considerably obese people does fat signi®-cantly contribute to overall conductance as recently analyzed by Baumgartner et al 23 The indirect approach renders the methods susceptible for interferences with all physiological quantities which determined the electrical properties of the well-conducting tissues, for example muscle.…”
Section: Introductionmentioning
confidence: 99%